INTERACTIVE EDUCATIONAL METHODS OF PHYSICAL EDUCATION AND FORMATION OF INNOVATIVE ACTIVITY (Scientific journal of the Fergana State University, 2023)
This article provides information on how to increase the level of professional knowledge of students, improve the literacy of young people based on new requirements, the introduction of a system of continuous education, the requirements of our time. Innovative educational technologies in teaching physical culture in the priority order consist in radical reforming of the existing education system, raising it to the level of modern requirements, building a new system, educating a harmonious, promising generation.